The Shiism Dimension in Iran's Relations with Europe: The Example of Germany-France-United Kingdom - Orhan Karaoğlu (Turkish Journal of Shiite Studies)
The phenomenon of religion appears as a multidimensional element in terms of individual, society and state. It has effects on people individually as well as in the context of social and international relations. In terms of states, religion appears as a phenomenon that affects and determines the domestic and foreign policies of states. Especially in the 21st century, we see that religion has begun to affect international relations in various areas. Another area where International Relations has begun to establish relations in recent years has been religion. Especially when foreign policy decision-making processes are examined, it is seen that religious beliefs, religion-based organizations and non-governmental organizations are effective in the decision-making processes of state administrators. The issue of Islamic Sects, and Shi’ism in particular, has been a much-discussed phenomenon in recent years due to its global and regional effects. Along with the Persian perspective inherited from the Persian Empire, Shi'ism has significantly influenced and continues to influence the geopolitical and geocultural education of today's Iran. With its politicization, Shiism has become one of the factors that play an important role in the creation and preservation of Iran's national identity, perhaps the most important. In this context, Iranian Shiism, which creates a socio-cultural system different from other civilizations around it, has become the main determinant on the security and foreign policy of today's Iran by intertwining with Persian nationalism since the reign of Shah Ismail. Iran has influenced Shiite communities in various regions - the Middle East, Africa - Central Asia - through its Shiite proxies, or has worked to Shiite the promising masses in the political field. Iran also has an influence on Shiite Muslims in Europe. Its relationship with the Shiite communities here appears as an important element in Iran's relations with European countries in the context of foreign policy. Shiite activities in Germany are carried out through an association in Hamburg, where Iranian business people have been living for many years. The Islamic Center of Hamburg describes itself as the "case representative" of the Shiites in Europe, especially in Germany. The concentration of Shiites and organizations in Germany in a single center is entirely in line with Iran's aim of "uniting the Shiites of the world under its rule and spreading Shiism (the belief in velayat-e faqih) from a single center". Approximately 200,000 Shiites live in France. Ten associations and cultural centers, which have been identified as carrying out religious activities on the basis of Shiism, are active in the country on behalf of Iran. Shiites currently constitute 10% of the total number of Muslims in the UK. Persian community centers have been established in the UK since the 1980s. Iranian individuals have established associations in the UK in many fields such as trade, health, culture and religion. It is estimated that these associations aim to spread Shiism among Muslim communities in the UK. Iran is trying to be active in Europe through these groups and Shiism is an important element in its relations with Europe.